Limb remote ischemic postconditioning protects cerebral ischemia from injury associated with expression of HIF-1α in rats. Issue 1 (December 2015) - Zong, Yonghua; Jiang, Ling; Zhang, Mingxiao; Zhou, Fangfang; Qi, Wenqian; Li, Shuai; Yang, Huijun; Zou, Yu; Xia, Qingjie; Zhou, Xue; Hu, Xiaosong; Wang, Tinghua
Abstract Background Limb remote ischemic postconditioning (LRIP) can ameliorate cerebral ischemia–reperfusion injury (IRI), while the underlying mechanism remains elusive. Hypoxia-inducible factor 1α (HIF-1α) is an important transcription factor during cerebral ischemia damage. However, whether the neuroprotective effect of LRIP could be associated with HIF-1α is somewhat unclear. Here we tested the hypothesis that Limb remote ischemic postconditioning (LRIP) protecting brain from injury in middle cerebral artery occlusion (MCAO) rat model was associated with HIF-1α expression. Results LRIP was conducted with 3 cycles of 10 min occlusion/10 min reperfusion at the beginning of reperfusion. The analysis of neurobehavioral function and triphenyltetrazolium chloride (TTC) staining showed the neurological deficit, brain infarct and cerebral edema, caused by ischemia–reperfusion injury (IRI), were dramatically ameliorated in LRIP administrated animals. Meanwhile, the result of Q-PCR and western blot revealed that the overexpression of HIF-1α induced by IRI could be notably suppressed by LRIP treatment. Conclusions LRIP exhibits a protective effect against cerebral ischemia/reperfusion and the possible mechanism is associated with the suppression of HIF-1α in stroke rats.